Historical study on the landuse change of hobby gardens in Esztergom from the 19th century to present-day - Molnárné Abicz, Kinga; Vaszócsik, Vilja (JOURNAL OF LANDSCAPE ECOLOGY, 2019)
In the period before the phylloxera outbreak (late 1800s to early 1900s), viticulture appeared as a dominant and almost exclusive form of cultivation in Esztergom, Hungary, as well as in many of the country’s settlements. The volcanic soil provided a favourable basis for vine growing traditions, which has been a decisive element of the landscape for centuries. Former vineyards classified as a special legal form as land ownership and land-use types were redefined in the 19th century, which marked agricultural use as its primary function. The focus of this study is on the creation and transformation of a special Hungarian concept, so called „hobby gardens”, between the 19th century and present-day in the Esztergom city area. The aim is to explore and discuss the processes related to the examination of the enclosed gardens at several different historical ages. The land-use and boundaries of hobby gardens have changed as a result of current socio-economic processes, some areas have been annexed to settlements and others have been classified as hobby gardens. The transformation process of the former vineyards into hobby gardens is characterized by the alternation of strong development and drastic decline. Extension of residential land-use was the primary reason for garden internalization, a kind of internal suburbanization. This special function agricultural land-use characterizes a valuable landscape and ecologicaleconomic area that should be conserved.
Keywords: periphery; plot gardens; vineyards; landuse; landscape change